2021
DOI: 10.1038/s41586-021-04024-x
|View full text |Cite
|
Sign up to set email alerts
|

The structure of neurofibromin isoform 2 reveals different functional states

Abstract: The autosomal dominant monogenetic disease neurofibromatosis type 1 (NF1) affects approximately one in 3,000 individuals and is caused by mutations in the NF1 tumour suppressor gene, leading to dysfunction in the protein neurofibromin (Nf1)1,2. As a GTPase-activating protein, a key function of Nf1 is repression of the Ras oncogene signalling cascade. We determined the human Nf1 dimer structure at an overall resolution of 3.3 Å. The cryo-electron microscopy structure reveals domain organization and structural d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 58 publications
2
26
0
Order By: Relevance
“…While individual domains of neurofibromin have been crystalized (D'angelo et al, 2006;Scheffzek et al, 1998), the overall architecture of the protein has long remained elusive. Recently, structures of neurofibromin solved by cryoelectron microscopy (cryo-EM) have revealed the dimeric architecture of this protein, which rests in an equilibrium between two conformational states (Lupton et al, 2021;Naschberger et al, 2021), including an autoinhibited closed conformation. However, the mechanism of neurofibromin activation remains unclear, impeded by lower resolution of the open-active conformation.…”
Section: Introductionmentioning
confidence: 99%
“…While individual domains of neurofibromin have been crystalized (D'angelo et al, 2006;Scheffzek et al, 1998), the overall architecture of the protein has long remained elusive. Recently, structures of neurofibromin solved by cryoelectron microscopy (cryo-EM) have revealed the dimeric architecture of this protein, which rests in an equilibrium between two conformational states (Lupton et al, 2021;Naschberger et al, 2021), including an autoinhibited closed conformation. However, the mechanism of neurofibromin activation remains unclear, impeded by lower resolution of the open-active conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Given that neurofibromin is a large molecule with numerous protein-binding domains and novel conformational states ( Naschberger et al, 2021 ), it is likely that other, perhaps RAS-independent, properties exist.…”
Section: Ras-independent Neurofibromin Functionmentioning
confidence: 99%
“…Although there is a wealth of information delineating the varied functions of neurofibromin in different cell types and tissues, most of these studies are focused on RAS pathway regulation. The recent elucidation of the physical structure neurofibromin revealed that it likely functions as a homodimer ( Lupton et al, 2021 ; Naschberger et al, 2021 ; Sherekar et al, 2020 ) with at least two distinct molecular conformations. In its closed, auto-inhibited conformation, RAS binding is blocked, thus inhibiting neurofibromin RAS-GAP activity.…”
Section: Neurofibromin Isoforms and Subcellular Localizationmentioning
confidence: 99%
See 2 more Smart Citations